Colonizing cuts of labyrinth mythology, a tangling parable of white sensibilities. Issue 1 (March 2020) - Keeling, Diane Marie
This article demonstrates the way wounds, and affects generally, are figured by the writing of history. It traces patterns of thinking about the labyrinth primarily in histories, theories, and myths of the past 150 years to demonstrate how the labyrinth has been cut by colonization. From the Mycenaean colonization of Indigenous Cretans (inaccurately named "Minoans") to the emergence of white feminism and its present day practice, figures of the labyrinth iteratively cut history to perpetuate the un/common loss of colonized communities and to enact white racist sensibilities of exclusion. Entangling Karen Barad's cutting together-apart and Kent Ono's colonial amnesia, colonizing cuts are constitutive exclusions that wound and exclude colonized communities from history and world making.